Pik. K Škirpos pasiūlymo Vokietijai ir Tarybų Sąjungai garantuoti Lietuvos nepriklausomybę bei parainą kovoje dėl Vilniaus klausimu - Locaitis, Linas (Lietuvos istorijos studijos, 1998)
In the 1930's, Colonel Kazys Škirpa served as Lithuania's military attaché in Berlin. His responsibilities included the representation of the Lithuanian Army, development and promotion of friendly relations between Lithuanian and German armies, and collection of information about the German army itself. However, very often during meetings with high-ranking German military staff officers, Colonel K. Škirpa not only discussed political problems that had arisen between Lithuania and Germany, but also spoke of a joint military action against Poland. He attempted to gain support from Germany and the Soviet Union in Lithuania's struggle to regain control of the Vilnius region.On one hand, Great Britain and especially France were strongly backing Poland in an attempt to achieve normal diplomatic relations with her eastern neighbor. On the other hand, the Lithuanian government was rejecting any diplomatic relations with Poland until the Vilnius region was returned. It was during this time that Lithuania looked to the German and Soviet governments for diplomatic support in her push to re-establish rule over the former Lithuanian capital.In the early 1930's, Germany turned its foreign policy towards an open revision of the Versailles peace accord. Such a change in German policy directly affected Lithuania by raising sharp German-Lithuanian pleadings within the International Tribunal in The Hague over Lithuanian policy in the Klaipėda region. Lithuanian-German relations were going to become worse.Due to widespread mistrust between the German and Lithuanian governments, Colonel K. Škirpa made the suggestion that both Germany and the Soviet Union should guarantee Lithuania's independence and actively support Lithuania in her fight for Vilnius.The article gives an overview of the circumstances under which such a suggestion by K. Škirpa took place. It also deals with the consequences that might have occurred if these suggestions had been accepted by the Lithuanian Foreign Ministry.